Extensive Exposure of Cadmium (Cd): A Silent Driver of Diabetes Epidemic beyond Testing of Blood Sugar in Pakistan - Qader, Abdul; Khaliq, Rabia; Hayat, Muhammad Khawar (Health Dynamics, 2025)
The prevalence of diabetes mellitus has been increased and our diagnostic strategies are limited to only body mass index (BMI), blood sugar level and life style changes. This is actually a silent driver which we ignored in diagnosis of diabetes mellitus. The elevated level of blood sugar tells us that our pancreas is struggling while high level of cadmium in urine and blood exhibits why pancreas is struggling. Until, we test blood and urinary cadmium levels we cannot reach the actual cause of high blood sugar level. Thus, we ignore a cause which should actually be removed. Therefore, the concentration of cadmium should not be ignored during the diagnosis of diabetes mellitus especially in big cities of Pakistan where exposure is on its peak level.